(untitled) (Reflection and Critique Law Magazine, 2022)
This article aims to address the main repercussions of the Statute of Persons with Disabilities in the notarial and registry activity. It deals with the intended equality, the benefits and mismatches of this law, as well as seeks to point out solutions to doubts that arose in the extrajudicial services before the aforementioned Statute. The present work brings up issues such as marriage, inventories and other everyday acts in extrajudicial services, but under the focus of the disabled person and their peculiarities, showing the fine line that exists, in the performance of the delegates of the extrajudicial service, between ensuring the free and spontaneous manifestation of the parties, devoid of coercion, and the wrongly unequal treatment for those who have some type of disability.